2009
DOI: 10.1111/j.1945-1474.2009.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

A STEMI Code Protocol Improves Door-to-Balloon Time on Weekdays and Weekends

Abstract: Primary percutaneous coronary intervention (PCI) has emerged as the standard of care for the management of ST-elevation myocardial infarctions (STEMI). Only 32% of patients with STEMI receive this procedure within the recommended 90 min for door-to-balloon time (DTB). We reviewed all STEMI cases that presented to our institution before and after the implementation of a STEMI Code protocol. Before the STEMI Code protocol, 27.1% of weekday cases and 6.3% of weekend cases were performed within 90 min. After the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Effect on door to balloon time: Increase = ↑, Decrease = ↓. [5,17,20,28,30,32,33,40,43,48,49,55,62,69,72,73,86] over no effect [38,98] Moderate…”
Section: Physician and Other Characteristicsmentioning
confidence: 95%
See 1 more Smart Citation
“…Effect on door to balloon time: Increase = ↑, Decrease = ↓. [5,17,20,28,30,32,33,40,43,48,49,55,62,69,72,73,86] over no effect [38,98] Moderate…”
Section: Physician and Other Characteristicsmentioning
confidence: 95%
“…than a cardiologist initially after the diagnosis of STEMI [85]. "Other" characteristics associated with longer door to balloon time include earlier year of PCI [18,34,41,[50][51][52]69,71] and "off hours" presentation [5,17,20,28,30,32,33,38,40,43,48,49,55,62,69,72,73,86,98]. While weekend or off-hours presentation was associated with longer door to balloon time in almost all reports, several authors reported that quality improvement protocols or initiatives can diminish or erase these differences [17,72].…”
Section: Physician Characteristicmentioning
confidence: 96%
“…Several studies have reported that the proportion of patients with AMI with door-to-balloon times <90 min varies, ranging from 6.3% to 98.5%. 14 20 Pan et al 9 showed that implementing specific strategies improved the proportion of patients who underwent PCI within 90 min from 59.4% to 98.5% ( p <0.001). On the other hand, our study did not show significant differences in the proportions of patients who underwent PCI within 90 min, regardless of the arrival time at the ED, ranging from 89.6% to 95.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies have suggested that the DTD time tends to be long in patients who arrive at the hospital at night or on the weekend . To address this problem, several measures for the improvement of the DTD time during off‐hours have been reported with successful results …”
Section: Introductionmentioning
confidence: 99%
“…6 To address this problem, several measures for the improvement of the DTD time during off-hours have been reported with successful results. 7 Notably, the DTD time is a part of the total ischemic time, and the latter is considered important as it reflects ischemic injury more precisely. In this regard, evaluation of the onset-to-device (OTD) time is considered as important as the subsequent DTD time.…”
Section: Introductionmentioning
confidence: 99%